SYNCHRONIZATION OF OVULATION IN POSTPARTUM SAHIWAL COWS - ALl, SARFRAJ; AWASTHl, M K; KHAN, J R; TIWARl, R P; BHONSLE, D; POYAM, M R (The Indian Journal of Animal Reproduction, 2023)
Present investigation was conducted to evaluate two different Ovsynch protocols for synchronization of ovulation in postpartum Sahiwal cows. Experimental animals (n=12) were randomly divided in to 2 groups; each group consisted of 6 animals. Animals of group I were treated with traditional Ovsynch protocol, while animals of group II were treated with a modified Ovsynch protocol where first GnRH injection was replaced with hCG. Treated animals were inseminated at fixed time of 14 to 20 hrs after second GnRH injection without estrus detection. Blood sample were collected from the experimental animals on days -10, 0, 8 and 16 of Ovsynch protocol (day60 postpartum = day O of Ovsynch protocol) to estimate serum progesterone concentrations. Animals were classified as cyclic (n=8, P4 e" 1ng/ml) and acyclic (n=4, P4 < 1ng/m1) based on serum progesterone concentration on days -10 and 0. Response to treatment was assessed in treated animals on the basis of progesterone concentration on day 8 (PG treatment); 83.3% (5/6) animals responded to first GnRH treatment in group I and 100% (6/6) animals responded to hCG treatment in group II. Two cyclic animals each from both the treatment groups got conceived to fixed time Al giving conception rate of 40% (2/5) in group I and 33.3% (2/6) in group II. Three cyclic and 4 acyclic animals did not conceive after responding to treatment, while one cyclic animal did not respond to first GnRH treatment. No any beneficial effect of replacing first GnRH injection with hCG could be obtained in ovulation synchronization and conception rate with Ovsynch protocol in Sahiwal cows during early postpartum period